Developing the Competence of Organizing Experiential Activities for Pre-service Teachers – The Case in Vietnam - Anh Mai Nguyen, Thi; Thuy Hoang, Thanh; Thuy An Le, Thi; Diu Luu, Thi; Hung Le, Quang; Thanh Hien Nguyen, Thi; Chien Nguyen, Van (International Journal of Psychosocial Rehabilitation, 2020)
Investing in human capital via enhancement of educational quality is one of the important factors to promote economic development all over the world. Basically, it is important to enhance pre-service teachers of primary education with the necessary professional competences to implement teaching activities at primary schools. Based on relevant research on experiential activities, professional competence development for pre-service teachers of primary education, and the general education curriculum in the case of Vietnam, the article develops a competency framework for organizing experiential learning activities for pre-service teachers of primary education in the context of education curriculum innovation and simultaneously suggests fundamental solutions to improve pre-service teachers’ competence in organizing experiential activities. To achieve these above-mentioned goals, some research methods are used by the researchers, including document analysis, pedagogical observation, and the educational experience summarizing method.